Residential Mortgage Default Risk and Market Returns of Public Mortgage Originator Firms in Kenya - Mwikamba Tumaini Mutugi; Willy M. Muturi; Oluoch J. Oluoch (European Scientific Journal, ESJ, 2020)
The mortgage market plays a vital role in the development of the real estate sector. The mortgage industry in Kenya has experienced tremendous growth since the year 2000. Despite this growth, Kenya’s mortgage debt to GDP ratio is still relatively low when compared to other economies like South Africa. Default risk has been revealed as one of the risks that significantly impacts on the profitability of mortgagees. However, literature is inconclusive with reference to the relationship between default risk and the market returns of mortgage firms. Consequently, this study sought to determine the extent to which residential mortgage default risk influences the market returns of publicly listed mortgage firms in Kenya. Default risk in this case was measured using the non-performing loans ratio: the ratio of non-performing residential mortgage loans to total residential mortgage loans and advances. The study adopted descriptive and quantitative forms of research design. A census was conducted on the eleven NSE listed mortgage originating firms. A panel data regression model was utilized to draw inference from the secondary data collected. Descriptive statistical findings revealed a mean of 0.0796 with a standard deviation of 0.04219 for residential mortgage default risk. Inferential statistics revealed an R square value of 0.2794 between residential mortgage default risk and market returns of publicly listed mortgage originators. In addition, there was significant effect between default risk and the market returns of public mortgage originators. Consequently, mortgagees should develop strategies of reducing nonperforming loans. For instance, mortgage firms can improve their credit rating systems.